2005
DOI: 10.1038/sj.ejcn.1602230
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of β-carotene, vitamins C and E, zinc and selenium are influenced by sex, age, diet, smoking status, alcohol consumption and corpulence in a general French adult population

Abstract: Objective: To assess relationships between energy, nutrient and food intakes, alcohol consumption, smoking status and body mass index (BMI), and serum concentrations of b-carotene, a-tocopherol, vitamin C, selenium and zinc. Methods: Data on health status, alcohol consumption, smoking habits, anthropometric data and biochemical measurements were obtained in 1821 women aged 35-60 y and 1307 men aged 45-60 y, participant to the SU.VI.MAX Study. Data on dietary intake were available on a subsample who reported si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

25
221
6
15

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(267 citation statements)
references
References 61 publications
25
221
6
15
Order By: Relevance
“…We found an inverse association between energy intake and serum retinol and -tocopherol concentrations. This is in agreement with some previous studies [45][46][47], but others have shown positive or no relation of energy intake to blood -tocopherol or retinol levels [14,47,48].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We found an inverse association between energy intake and serum retinol and -tocopherol concentrations. This is in agreement with some previous studies [45][46][47], but others have shown positive or no relation of energy intake to blood -tocopherol or retinol levels [14,47,48].…”
Section: Discussionsupporting
confidence: 82%
“…It is similar with results of others, who also observed that low intakes of alcohol have not been related to a decrease of antioxidant vitamins in the human body [14,45,47,54]. It is known that alcohol may increase oxidation of -tocopherol and retinol and reduce body stores [12,54,60], but the oxidative stress by alcohol depends on the amount and frequency of alcoholic beverage consumed [61,62].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Galan et al reported significantly lower plasma levels of vitamin A and C and insignificantly lower plasma levels of vitamin E in the French adult population in a group of obese subjects compared to healthy individuals [31].…”
Section: Discussionmentioning
confidence: 99%
“…12 Nevertheless, levels of these biomarkers have also been suggested to be correlated to gender, age and smoking status, with lower levels of vitamin C and carotenoids in smokers and higher levels in women, especially younger women. [13][14][15] In the studies included in the WCRF report, dietary intake was assessed by dietary questionnaires and concentrations of vitamins in foods were calculated using food composition tables. These methods are, however, prone to measurement error and may not fully take into account the bioavailability of dietary nutrients.…”
mentioning
confidence: 99%